Increasing The Character of Courage In Early Childhood Through Mother Tongue - Dwi Putriyanti; Issaura Dwi Selvi (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
Each child has a different character. In this case, the role of the family, especially the mother, is very supportive of the child in instilling the child's character according to his potential. The purpose of this study was to improve the character of children's courage through their mother tongue by using the classroom action research method conducted at Aisyiyah Bustanul Athfal Kindergarten in Sungai Pinang Ogan Ilir by researching two cycles consisting of 3 meetings with planning, implementation, observation and reflection stages. Based on the research results in the first cycle, the minimum category developed as expected 67%, with the dominant indicator appearing as the attitude of doing something without worrying about the difficulties. In comparison, the minimum category increased to 87% in the second cycle, indicating that the child can face something with great confidence and great results. This shows that using the mother tongue can improve the character of the courage of early childhood.